The synthesis and structural characterization of polycyclic derivatives of cobalt bis(dicarbollide)(1(-)) - Grüner, Bohumír; Šícha, Václav; Hnyk, Drahomír; Londesborough, Michael G S; Císařová, Ivana (Inorganic chemistry, 2015)
The cobalt bis(dicarbollide) anion [(1,2-C2B9H11)2-3,3'-Co](-) (1(-)) is an increasingly important building block for the design of new biologically active compounds. Here we report the reactions of lithiated 1(-) with N-(ω-bromoalkyl)phthalimides Br-(CH2)n-N(CO)2NC6H4 (where n = 1 to 3) that give a number of new compounds substituted at dicarbollide carbon atom positions. For n = 2 and 3, substitution of the cobalt bis(dicarbollide) anion is accompanied by cyclocondensation of the organic moieties to give polycyclic ring structures attached to the cage. Predominant products correspond to oxazolo[2,3-a]isoindol-5(9bH)-1,2,3-dihydro-9b-yl)-(1-cobalt(III) bis(1,2-dicarbollide)(1(-)) (2(-)) and 1-(2H-[1,3]-oxazino[2,3-a]isoindol-6(10bH)-1,3,4-dihydro-10b-yl)-(1-cobalt(III) bis(1,2-dicarbollide)(1(-)) (4(-)) ions with isoindolone functions containing either five- or six-membered lateral oxazine rings. Additionally, products (tetrahydro-2-benzo[4,5]furan-1(3H)-1-[3,3]-yl-)-1,1'-μ-cobalt(III) bis(1,2-dicarbollide)(1(-)) (3(-)) and (2-(azetidin-yl-carbonyl)benzoyl-)-1-cobalt(III) bis(1,2-dicarbollide)(1(-)) (5(-)) were isolated, which display unusual cyclic structures featuring a bicyclic benzofuranone ring attached in a bridging manner by a quarternary carbon to two skeletal carbon atoms and a ketobenzoic acid amide substituent with a side azetidine ring. However, in the case of n = 1, only the anticipated methylene amine derivative [(1-NH2CH2-1,2-C2B9H11)(1',2'-C2B9H11)2-3,3'-Co](-) (6(-)) was isolated in low yield after cleavage of the phthalimide intermediate species. The molecular structures of all isolated cyclic products 2(-) to 5(-) were confirmed by single-crystal X-ray diffraction studies, and the structure of cobalt bis(dicarbollide)-1-CH2NH2 6(-) was delineated using density functional theory applied at BP86/AE1 level in combination with NMR spectroscopy. Thus, the synthetic method described herein presents a facile route to new cobalt bis(dicarbollide) derivatives substituted by polycyclic structural motifs with potential biological activity.